5 - Le travail domestique : occultation de la personne et de catégories de genre existantes: Melchicedec Nduwayezu, Salvator Nahimana &Célestin Mvutsebanka - Melchicedec Nduwayezu,; Salvator Nahimana,; Célestin Mvutsebanka, (African Sociological Review, 2021)
Domestic work is presented in literature and the social representations as an essentially female occupation and taking place in the private realm. The development of this sector of activities and its current situation in Burundi and the sub-region questions the theoretical assumptions often mobilized to describe and explain the phenomenon. The article highlights the limits of a still western-centered vision of domestic work and spark a new debate on the issue in the light of current developments in the sphere of salaried work. This study is based on ethnographic data produced in the Burundian field. As in other countries of the African Greats Lakes Region, there are almost as many men as women in this kind of work. These workers are pushed to engage in this kind of activity because of the precarious conditions in which they find themselves and their families. The article thus extends the interest in the study of marginal categories and therefore questions the domestic work through the prism of gender categories. Moreover, given that this work constitutes a type of social relationship, the article opens up avenues for research on gender and domesticity in their articulation of both marital relationship and those taking place in classic salaried work.